Identifying the manufacturing industrial clusters in the districts of T?rkiye - Sakarya, Adem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
This article identifies the manufacturing industry clusters in Turkiye and contributes to the literature by identifying clusters at the district level. The literature background of this study is based on the concept of cluster and cluster identification. The study uses the sales and purchases between manufacturing industries via the input-output tables of 24 manufacturing industries and the number of employment and workplaces in each industry at the district level for 2019 as data. The methodology consists of three steps: the study first identifies the purchase and sales relations between industries, then groups related industries using principal component factor analysis, and lastly determines the spatial concentration of industries using the location quotient. The study's findings show manufacturing industries to be grouped into six cluster templates. The districts where industries are clustered are mostly located in the western Turkiye. The textile industry differs because it is clustered in southeast Turkiye. The geographical distributions of the furniture industry clusters and non-metallic industry clusters also differ due to having different location criteria. The packaged food industry is clustered in more districts compared to all other industries except the non-metallic industry, and the districts are located in highly populated provinces. These results place a comprehensive framework across the country and can enable policymakers to direct cluster policies.
Keywords: Key Cluster identification; cluster policy; industrial clusters; manufacturing industry; T?rkiye; IDENTIFICATION; TEMPLATES; LOCATION; Architecture